Fatty Acid Profiling of Moina sp. Preserved in Cryoprotective Agents at Low Temperature - Dr. Nurul Ulfah Karim; Muhammad Fathi Sofian; Hanan Yusuf; Abu Hena Mustafa Kamal (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
Highlight ResearchSaturated fatty acid (SFA), polyunsaturated fatty acid (PUFA), âˆ‘ Ï‰6 and âˆ‘ Ï‰3 of Moina sp. preserved with 5, 10 and 20% GLY decreased with prolong storage.FA of Moina sp. preserved with 5, 10 and 20% EG showed a significant reduced only after M3.Monounsaturated fatty acid (MUFA) and PUFA of Moina sp. preserved with 5, 10 and 20% DMSO increased significantly (p<0.05) after M3.Moina sp. preserved in 5% DMSO maintain the docosaheaenoic acid (DHA) level, which could be potential method for long-term preservation.AbstractMoina sp. is an important feed for larval and post-larval rearing of aquaculture species. Preservation of Moina sp. using various preservation agents and techniques is known to be less time-consuming procedure in maintaining large number of feed in hatchery management. Hence, this study was carried out to determine the changes of fatty acid (FA) composition of Moina sp. preserved at 5, 10 and 20% in glycerol (GLY), ethylene glycol (EG) and dimethyl sulfoxide (DMSO) for 1 to 3 months (M1-M3). Moina sp. without cryoprotectant agents stored at -40°C as controls. Saturated fatty acid (SFA), polyunsaturated fatty acid (PUFA), âˆ‘ Ï‰6 and âˆ‘ Ï‰3 of Moina sp. preserved with 5, 10 and 20% GLY decreased with prolonging storage. FA of Moina sp. preserved with 5, 10 and 20% EG showed a significant reduction only after M3. Monounsaturated fatty acid (MUFA) and PUFA of Moina sp. preserved with 5, 10 and 20% DMSO increased significantly (p<0.05) after M3. Moina sp. preserved in 5% DMSO maintain the docosaheaenoic acid (DHA) level, which could be a potential method for long-term preservation.